Driving Helical Packing of a Cyanine Dye on Dendron Nanofiber: Gel‐Shrinkage‐Triggered Chiral H‐Aggregation and Enhanced Enantiodiscrimination. Issue 32 (19th June 2015) - Qin, Long; Xie, Fan; Jin, Xue; Liu, Minghua
Abstract: An intelligent molecular hydrogel with a volume phase transition was constructed to regulate the chiral packing of a well‐known cyanine dye on a dynamically self‐assembled chiral nanofiber by using a pH trigger. During the shrinkage of the gel, the chiral nanofiber hierarchically assembled into a superhelix and simultaneously drove the dye molecules to stack, from a predominantly monomer form, in an unexpected helical H‐aggregation manner. Through such a transformation, the supramolecular chirality of the system was significantly enhanced and a new property of visual discrimination for chiral amines emerged. Abstract : Chiral packing : Hydrogel volume phase transitions with a pH trigger cause the chiral packing of pseudoisocyanine to form unexpected H‐aggregates on chiral dendron nanofibers. Through gel shrinkage, the supramolecular chirality of the aggregates was significantly enhanced and a novel property of visual discrimination of chiral amines emerged.